Modelagem da propagação de pressão no reinício do escoamento de fluidos de perfuração não gelificados - Oliveira, Gabriel Merhy de (2011)
The fluid flow start-up is a significant problem in deepwater and in long wells such as those of the Brazilian subsalt layers. Depending on the well geometry and fluid properties, significant pressure peaks may take place affecting the wellbore structure. This work presents a mathematical model to simulate the transient and compressible flow start-up of drilling fluids so as to predict the pressure transmission along the well and the pressure peak during the flow start-up. The model is based on the conservation equations of mass and momentum which are solved by the method of characteristics. Drilling fluids are treated as non-newtonian Bingham fluids and viscous effects are considered by using the friction factor approach. The model results are corroborated with some experimental values for a Newtonian (water) and two drilling fluids. Case studies are conducted to verifying how the magnitudes of the pressures peaks are affected by the fluid properties and the well geometry. The magnitude of the pressure peak is related to the phenomenon of superposition of pressure waves that are reflected in the ends of the drillpipe-well geometry. Either increasing the well length, viscosity, yield stress and fluid compressibility, or decreasing the fluid density and the cross-sectional area, the pressure wave is faster dissipated. The lower the pressure wave dissipation by viscous friction larger is the magnitude of the pressure peak in the borehole. For constant inlet flow rates as boundary condition, the magnitude of the peaks decreases as the ratio of the pipe and well cross-sectional areas increases, whereas for constant inlet pressure cases, this peak reaches a minimum value.